Disrupting β-Catenin/BCL9 interaction with a peptide prodrug boosts immunotherapy in colorectal cancer - Wang, Peili; Shang, Xiao; Wang, Jinmei; You, Weiming; Qu, Shoufei; Yao, Yu; Zheng, Xiaoqiang (Frontiers in Immunology, 2025)
IntroductionHyperactivation of the Wnt/β-catenin pathway serves as a central mechanism underlying tumor progression, immune evasion, and resistance to immune checkpoint inhibitor therapy in colorectal cancer (CRC). A pivotal contributor to this process is the binding of β-catenin to B-cell lymphoma 9 (BCL9), which promotes transcription of oncogenes and fosters an immune-suppressive tumor milieu. Consequently, targeting this interaction offers a promising approach to suppress tumor progression and potentiate antitumor immune responses.MethodsWe developed a peptide-based prodrug, Bcl9@TP, designed to competitively bind the BCL9 interface on β-catenin, destabilize the transcriptional complex, and suppress Wnt/β-catenin signaling. Its antitumor efficacy and immune potentiation were assessed in vitro using MC38 cells and in vivo in murine tumor models.ResultsIn vitro, Bcl9@TP significantly inhibited MC38 cell proliferation by downregulating β-catenin and its downstream targets, inducing G1-phase cell cycle arrest. In vivo, Bcl9@TP treatment markedly reduced tumor burden, with a tumor growth inhibition (TGI) rate of 62%, significantly higher than the control group. In contrast, anti-PD-1 monotherapy yielded a TGI of only 41%. Notably, combination therapy (Bcl9@TP plus anti-PD-1) produced a more pronounced antitumor effect, with the TGI reaching 82%. Importantly, Bcl9@TP demonstrated favorable systemic biocompatibility and safety.DiscussionOur findings indicate that disrupting the β-catenin/BCL9 interaction with a peptide-based nanoprodrug represents a compelling strategy to suppress oncogenic signaling and enhance immunotherapy responses in CRC, providing a new angle to boost checkpoint sensitivity.